EFEKTIVITAS IMPLEMENTASI PENDIDIKAN KARAKTER BERBASIS LITERASI ABAD 21 DI MTs NEGERI 2 LABUHANBAT - Nasution, Zilfaizah; Amini, Amini; Prasetia, Indra (Universitas Islam Negeri Sumatera Utara Medan, 2023)
The purpose of this study was to determine the effectiveness ofimplementing 21st century literacy-based character education at MTsNegeri 2 Labuhanbatu.This research is a qualitative research in the form ofa case study. This research was conducted at MTs Negeri 2 Labuhanbatu.The respondents of this study were school principals, vice principals,teachers and students. Data collection techniques by observation,interviews and documents. The results of this study are that MTs Negeri 2Labuhanbatu has implemented character education based on literacy aswell as culture and citizenship well by making careful learning plans.Where madrasas have developed planning and learning systems throughliteracy programs that can explore the intelligence and noble character ofstudents, MTs Negeri 2 Labuhanbatu has implemented quite wellprograms implementing literacy-based character education based onliteracy literacy as well as culture and citizenship and trying to improveprograms so that it can be more easily implemented by teachers andstudents. Character education based on literacy as well as culture andcitizenship is implemented by habituating students at MTs Negeri 2Labuhanbatu. so that students are directly able to obtain and applycharacter education to themselves so as to create output of students whohave good character, are noble, and have a sense of love for culture and thehomeland. The implementation of the literacy program at MTs Negeri 2Labuhanbatu for literacy literacy in schools includes providing readingcorner facilities in each classroom, reading garden facilities, and a library.As for cultural literacy and citizenship, there are extracurricular cultures,scouts and nationalities.Keywords: er Education, 21st Century Literacy, and Literacy in Literacy, and Culturaland Citizenship Literacy